Gestión docente y su incidencia en el rendimiento académico en los estudiantes de la unidad de admisión de la Universidad Técnica Estatal de Quevedo, segundo semestre 2015 - Navia Álava, Jaime Gerardo (2016)
La Universidad Técnica Estatal de Quevedo – UTEQ, is a higher education center; and attendance system with semi - face on the third level, also offer master's degrees; in this sense the Ecuadorian university has the fundamental mission to train professionals to be inserted in the workplace; among its functions is also training both teachers and administrative staff and service. The national education system seeks higher education gets its rightful role, all academic activities of the management, the same that addresses all components of education. Management involves preparation, it is the beginning of the academic activity, is an important development in pursuit of excellence in different areas including research element. Teaching management is part of the academic management, still teaching in Higher Education Institutions - IES, a cornerstone in the process of educational development. La Universidad Técnica Estatal de Quevedo – UTEQ, has Intake Unit and Leveling - UAN, the latter where this research was conducted; thus students of the centers of secondary education at the present time to enter university must first join the UAN, who pass the course leveling become part of the university ranks and in this case the UTEQ; the leveling system in higher education institutions, runs this process with college rigor. This study showed that the UAN of UTEQ, has a system quite successful in the discretion of the user, ie course participants UAN the second half of 2015, they stated that academic process and teaching the role of teachers UAN have clear their activities and actions enacted in the development of activities in the classroom, this means that teachers of this unit carry out their activities according to the instructions of the National System of Equalization Admission - SNNA, however, feedback to teachers of this unit have a thorough preparation in monitoring and motivation for the development of academic activities because the level of study is forced by the time students must remain at the center of study is always necessary and the classroom, so the motivation is necessary and permanent. It is important as a result of this research teaching action plan, which should apply UAN in the coming academic to develop periods.